ALIANÇA ESTRATÉGICA INTERSETORIAL: UM ESTUDO DE CASO DO FÓRUM PERMAMENTE DE DESENVOLVIMENTO REGIONAL DE PARANAVAÍ-PR - Vaz, Fábio Oliveira (2014)
Intersectoral strategic alliances, regional development and decentralization of government state are the focus of study in this dissertation. The decentralization of government through the participation of society in regionalized decisions have changed the form of management and formed unique identities of each regional group. The main objective of the study is to seek to know the strategic alliances formed between sectors from Paraná / PR and northwestern Paraná economy, comprising 28 municipalities, with the participation of representatives from each participating city and sector meetings and decisions taken by the Forum Development. The aim is also to identify the motivating training Development Forum report and its importance in business, society and state. Through a script semi-structured interview was possible to identify the effectiveness of strategic alliances and the problems that must be corrected. A documentary analysis was buying actions and results achieved by the Development Forum. This is an exploratory and descriptive qualitative study. The study aims to contribute to the management of regional development and the growth of industries in the locality, as well as expanding the dialogue on the subject.